The relationship between modeling, caregiver education and diverse diet in Costa Rican preschool children - Rodríguez Arauz, Gloriana (2025)
Previous literature shows that demographic characteristics of caregivers such as educational level, determine health processes in young children. However, the mechanisms through which educational level increases health in this population has been scarcely explored in low and middle-income countries (LMIC). Evidence also suggests that caregivers who model healthy eating to their children, such as eating healthy foods in front of them or enjoying the consumption of healthy foods, increase the likelihood that their child will do the same; Methods: Eighty-two primary caregivers of children between 3 and 5 years of age in Costa Rica completed an electronic questionnaire with measures on highest educational level attained, modeling of healthy eating and diet diversity of the children. Diet diversity indicates the intake of 7 important groups of macronutrients that are needed for healthy development in Costa Rican children. Results: To investigate these relationships, a simple mediation analysis was carried out, with diet diversity as an outcome, caregiver educational level as predictor, and modeling as mediator. The indirect effect of educational level on diet diversity was found to be statistically significant [Effect size =0.10, 95% C.I. (0.01-0.20)]; Conclusions: Results indicate that high educational level is associated with increased usage of healthy eating modeling with children, and this in turn is positively related to their diet being more diverse. Results suggest that modeling of healthy eating could be the object of interventions aimed at preventing obesity in Costa Rican children.